Catalogues of voids as antihaloes in the local Universe - Desmond, H; Hutt, ML; Devriendt, J; Slyz, A (Oxford University Press, 2022)
A recently proposed algorithm identifies voids in simulations as the regions associated with haloes when the initial overdensity field is negated. We apply this method to the real Universe by running a suite of constrained simulations of the 2M++ volume with initial conditions inferred by the BORG algorithm, along with the corresponding inverted set. Our 101 inverted and uninverted simulations, spanning the BORG posterior, each identify ∼150 000 ‘voids as antihaloes’ with mass exceeding 4.38 × 1011 M⊙ (100 particles) at z = 0 in a full-sky sphere of radius 155 Mpc h−1 around the Milky Way. We calculate the size function, volume filling fraction, ellipticity, central density, specific angular momentum, clustering, and stacked density profile of the voids, and cross-correlate them with those produced by VIDE on the same simulations. We make our antihalo and VIDE catalogues publicly available.